Simultaneous recipient external iliac endarterectomy and renal transplant – a propensity score matched analysis. (2nd December 2019) - Spaggiari, Mario; Okoye, Obi; Almario, Jorge; Tulla, Kiara; Di Cocco, Pierpaolo; Benedetti, Enrico; Tzvetanov, Ivo
Summary: Patients with end‐stage renal disease and severe iliac atherosclerosis are frequently denied renal transplant due to technical challenges, and risk of potential steal syndrome in the allograft, or ipsilateral limb. Few studies have evaluated the safety and efficacy of performing an endarterectomy in this setting. A single‐center retrospective review of renal transplant patients from 1/2013 to 12/2017 was performed. Patients requiring endarterectomy at the time of transplant were matched to a nonendarterectomized cohort in a 1:2 fashion using propensity score matching. Patients were followed for a minimum of 12 months. Simultaneous endarterectomy and renal transplant were performed in 23 patients and subsequently matched to 42 controls. Ankle‐brachial index was lower in the endarterectomized group ( P  = 0.04). Delayed graft function (26.1% vs. 19%, P  = 0.54), graft loss (8.7% vs. 7.1%, P  = 0.53), 1‐year mortality (8.7% vs. 4.8%, P  = 0.53), and renal function at 12 months were comparable in both groups. There were no incidents of ipsilateral limb loss in the endarterectomized population. This is the first matched study investigating endarterectomy and renal transplant. Long‐term follow‐up of limb and graft function is indicated. Despite the small sample size, our findings suggest that a combined procedure can safely provide renal transplantation access to a previously underserved population.